Increasing Quality of Life in Patients with Hemodialysis through Education Based on Self-Efficiency Theory - Fermata Sari; Lindesi Yanti; Ahmad Badaruddin (Indonesian Journal of Global Health Research, 2021)
Chronic kidney disease patients with hemodialysis cause lifestyle changes, one of which is fluid restriction. Poor management of fluid restriction can lead to increased cardiovascular mortality, morbidity, and decreased quality of life. To improve the quality of life in patients with hemodialysis is provide education based on the theory of self-efficacy so that it can increase the patient's self-confidence to carry out self-management. The purpose of this study was to determine the effect of providing educational interventions based on the theory of self-efficacy on quality of life in hemodialysis patients. This type of research is a quantitative research design One-Group Pretest-Posttest Design and the approach used a Kidney Disease Quality Of Life Short Form 1.3(KDQOL-SF1.3) quistionnare. The instrument consists of 19 domains which are grouped into three domains, namely the physical health component (PCS), the mental health component (MCS) and the kidney disease component (KDCS).The number of samples in this study was 34 people with the sampling method, namely probability using a simple random sampling technique. The results of the paired sample T-test on quality of life P-value 0.000 (< 0.05). The conclusion of education based on self-efficacy theory is that it is effective in improving the quality of life and can be used as consideration for educational innovations in hemodialysis patients in hospitals in improving the quality of life.